Correlation of Admission Time Blood Glucose, Left Ventricular Function and Regional Wall Motion Index with Occurrence of In-hospital Major Adverse Cardiac Events in Acute Coronary Syndrome - Swathi Gurursamy; Arunprasath Palamalai; Lokesh Shanmugam; Kalaimani Sivamani (Journal of Clinical and Diagnostic Research, 2020)
ABSTRACT Introduction: Admission time hyperglycaemia is associated with larger infarct size and increased inflammatory process in patients with Acute Coronary Syndrome (ACS). Patients with severe and moderate Left Ventricular (LV) dysfunction are more likely to have triple vessel disease. Admission blood glucose along with conventional Echocardiography (Echo) is a cost-effective and easily feasible method compared to N-terminal proB-type natriuretic peptide (NT-proBNP) in predicting Major Adverse Cardiac Events (MACE) in ACS. Aim: To study the correlation of admission time blood glucose, LV systolic function and Regional Wall Motion Index (RWMI) with in-hospital MACE in patients with ACS. Materials and Methods: This was a cross-sectional study which included 100 patients with ACS. Blood samples were taken immediately after admission for plasma blood glucose levels and 2D echo was done within 24 hours to assess LV systolic function and RWMI. All the 100 patients were observed for in-hospital MACE events like cardiac arrhythmias, cardiogenic shock, Congestive Cardiac Failure (CCF), LV dysfunction, recurrent angina and death. Chi-square test was carried out to look for statistical significance between clinical and demographic parameters. Results: The mean age was 55.4±11.2 years. The incidence of admission time hyperglycaemia was significant in patients with history of Diabetes Mellitus (DM). A total of 55 patients (87.3%) with history of diabetes and 12 patients (32.4%) patients with no previous history of diabetes had admission time hyperglycaemia and five patients had stress hyperglycaemia. There was statistically significant correlation of admission time hyperglycaemia with LV systolic dysfunction (p-value=0.02) and CCF (p-value=0.02). RWMI had statistically significant correlation with LV systolic dysfunction (p-value <0.001), CCF (p-value=0.008) and recurrent angina (p-value=0.02). There was statistically significant correlation of LV systolic function with recurrent angina (p-value=0.04) and death (p-value=0.005). Conclusion: RWMI and poor LV systolic function can predict the occurrence of in-hospital MACE in patients with ACS. In addition to echocardiography, raised blood glucose levels at the time of admission have a positive predictive outcome with higher incidence of MACE.